Hubungan Kebiasaan Konsumsi Jajanan dan Aktivitas Fisik dengan Status Gizi pada Remaja Usia 13-18 Tahun di Kelurahan Nunu: The Relationship Between Snack Consumption Habits and Physical Activity with Nutritional Status Among Adolescents Aged 13–18 Years in Nunu Subdistrict - Ramadhan, Doni; Imansari, Adillah; Nurdiana (UNIVERSITAS NGUDI WALUYO, 2025)
Adolescents are an age group that is vulnerable to nutritional problems, including both undernutrition and overnutrition. Two factors that commonly influence the nutritional status of adolescents are the habit of consuming high-calorie, low-nutrient snacks and low levels of physical activity. This study aims to analyze the relationship between snacking habits and physical activity with the nutritional status of adolescents aged 13 to 18 years in Nunu Subdistrict. This study employed a quantitative approach with a cross-sectional design. The population consisted of 1,107 adolescents, with a sample of 91 respondents selected using a cluster sampling technique. Data were collected through interviews and questionnaires, including a Food Frequency Questionnaire (FFQ) and Physical Activity Level (PAL) assessment. The independent variables were snacking habits and physical activity, while the dependent variable was nutritional status. Bivariate analysis was conducted using the Chi-Square test. Among the respondents with frequent snacking habits, 70.3% were classified as having excess nutritional status, while 49.3% of those with light physical activity also had excess nutritional status. Overall, 56% of respondents had normal nutritional status, 37.4% had excess nutrition, and 6.6% were undernourished. There was a significant relationship between snacking habits (p = 0.00) and physical activity (p = 0.02) with nutritional status. There is a significant relationship between snacking habits and physical activity with the nutritional status of adolescents aged 13–18 years in Nunu Subdistrict. ABSTRAK Remaja merupakan kelompok usia yang rentan terhadap masalah gizi, baik gizi kurang maupun gizi lebih. Dua faktor yang sering memengaruhi status gizi remaja adalah kebiasaan konsumsi jajanan yang tinggi kalori dan rendah nutrisi, serta rendahnya aktivitas fisik. tujuan penelitian yaitu Menganalisis hubungan kebiasaan konsumsi jajanan dan aktivitas fisik dengan status gizi pada remaja usia 13–18 tahun di Kelurahan Nunu. Penelitian ini bersifat kuantitatif dengan desain cross-sectional. Populasi berjumlah 1.107 remaja, dengan sampel 91 responden yang dipilih menggunakan teknik cluster. Data dikumpulkan melalui wawancara dan kuesioner (FFQ dan PAL). Variabel independen adalah kebiasaan konsumsi jajanan dan aktivitas fisik, sedangkan variabel dependen adalah status gizi. Analisis bivariat menggunakan uji Chi-Square. Responden dengan kebiasaan jajan sering sebanyak 70,3% yang berstatus gizi lebih, dan aktivitas fisik ringan sebesar 49,3% pada status gizi lebih. Status gizi responden menunjukkan 56% gizi normal, 37,4% gizi lebih, dan 6,6% gizi kurang. Terdapat hubungan signifikan antara kebiasaan konsumsi jajanan (p=0,00) dan aktivitas fisik (p=0,02) dengan status gizi. Terdapat hubungan antara kebiasaan konsumsi jajanan dan aktivitas fisik dengan status gizi remaja.